DOI: 10.14264/uql.2015.434
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference in early branching metazoans

Abstract: The RNA interference (RNAi) repertoire of metazoans is principally composed of three independent but related systems -endogenous small interfering RNAs (endosiRNAs), micro RNAs (miRNAs) and Piwi-interacting RNAs (piRNAs). Although the endosiRNA pathway has been demonstrated in all five eukaryotic supergroups, the miRNA and piRNA pathways of metazoans likely evolved subsequent to metazoan divergence from other eukaryotes. These innovations evolved in a 100-200 million year period between the emergence of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 254 publications
(411 reference statements)
0
2
0
Order By: Relevance
“…piRNAs with a bilaterian-like ping-pong piRNA biogenesis signature [a bias for a 5' uracil and an adenosine at position 10 (Brennecke et al, 2007;Czech and Hannon, 2016;Gunawardane et al, 2007)] have been reported in cnidarians, sponges and ctenophores, but not in placozoans (Calcino, 2015;Grimson et al, 2008), suggesting the piRNA pathway was a regulatory feature of the last common ancestor of animals.…”
Section: Animal Rna Interference Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…piRNAs with a bilaterian-like ping-pong piRNA biogenesis signature [a bias for a 5' uracil and an adenosine at position 10 (Brennecke et al, 2007;Czech and Hannon, 2016;Gunawardane et al, 2007)] have been reported in cnidarians, sponges and ctenophores, but not in placozoans (Calcino, 2015;Grimson et al, 2008), suggesting the piRNA pathway was a regulatory feature of the last common ancestor of animals.…”
Section: Animal Rna Interference Pathwaysmentioning
confidence: 99%
“…sRNAs expressed at the same four developmental stages as lncRNAs were used (Calcino, 2015;Grimson et al, 2008). The number of sRNAs overlapping lncRNAs was counted using overlapSelect with a 95% threshold.…”
Section: Srna Analysismentioning
confidence: 99%